Extrapelvic endometriosis: the mystery of the "black square" or "quintessential classics"? - Mekan R. Orazov; Viktor E. Radzinsky; Evgeny D. Dolgov; Yuliya G. Abramashvili (Гинекология, 2023)
Endometriosis is still one of the most mysterious and urgent gynecological diseases. The prevalence of endometriosis is steadily increasing, despite the development of innovative methods of diagnosis and treatment. Endometriosis is the presence of a heterotopic endometrium outside the uterine cavity and most often affects the pelvic organs. However, more and more often, the world medical community actualizes the study of extrapelvic endometriosis as a unique clinical entity with specific pathogenetic patterns, approaches to verification, and therapeutic concepts. The article summarizes and systematizes the current scientific data on pathogenesis, clinical phenotypes, and therapy of extrapelvic endometriosis.